Analysis of Junior High School Students' Scientific Argumentation Skills in Argument-Driven Inquiry (ADI) Learning Based on Gender - Zakaria, Zaky; Singgih, Suwito; Dewantari, Nuryunita; Suryandari, Suryandari (FKIP Universitas Lampung, 2025)
Scientific activities, such as communication, are essential skills in the 21st century. Scientific argumentation is a fundamental component of communication and serves as a foundation for students to engage in a series of scientific processes, leading to valid conclusions based on empirical data. This study aims to examine whether there are differences in the scientific argumentation abilities of male and female students following the implementation of Argument-Driven Inquiry (ADI) learning, as well as to analyze their respective argumentation patterns. This study employs an experimental research design with a pretest-posttest experimental group approach. The sample was selected using a purposive sampling technique. Data collection involved pretest and posttest scores. The analysis of research results was tested using Inter-Rater Reliability (IRR), score conversion, normality test, Mann-Whitney test, and N-Gain test. The study population consisted of eighth-grade students at SMP IT Ihsanul Fikri Mungkid, from which two classes were selected through purposive sampling: VIII D (experimental class 1 - male students) and VIII H (experimental class 2 - female students). The findings indicate that the ADI model effectively enhances students’ scientific argumentation skills in both experimental groups. The N-Gain analysis revealed that in the argument completeness aspect, experimental class 1 (male students) achieved an N-Gain of 0.70 (moderate category), whereas experimental class 2 (female students) scored 0.93 (high category). In the scientific validity aspect, experimental class 1 obtained an N-Gain of 0.63 (moderate category), while experimental class 2 scored 0.84 (high category). Regarding overall scientific argumentation, experimental class 1 achieved an N-Gain of 0.67 (moderate category), whereas experimental class 2 reached 0.82 (high category). Further analysis of the argument completeness aspect identified a statistically significant difference between male and female students (p < 0.05); However, in the scientific validity aspect, no significant difference was observed between male and female students (p > 0.05); In the overall scientific argumentation aspect, a significant difference was found between male and female students (p < 0.05). Keywords: gender, scientific argumentation, argument driven inquiry (ADI).